Hydrogen-bond driven supramolecular chemistry for modulating physical properties of pharmaceutical compounds - Forbes, Safiyyah (Kansas State University, 2010)
The ability to predict and control molecular arrangements without compromising the individual molecules themselves still remains an important goal in supramolecular chemistry. This can be accomplished by establishing a hierarchy of intermolecular interactions such as hydrogen and halogen bond, which may facilitate supramolecular assembly processes. Several acetaminopyridine/acetaminomethylpyridine supramolecular reactants (SR’s) were prepared with aliphatic carboxylic acids in order to determine patterns of molecular recognition preferences of the N-H moiety. The results obtained revealed the formation of molecular cocrystals through heteromeric O-H…N/N-H…O hydrogen bonds with the acetaminopyridine/acetaminomethylpyridine binding site. Furthermore, the SR’s also reacted with metal ions resulting in robust 1D and 2D metal-containing architectures. A series of pyridyl/pyrazine mono-N-oxide compounds were synthesized and reacted with a variety of halogenated benzoic acids, in order to assess the ability of these molecules to establish binding selectivity when both a hydrogen and halogen bond donor is present. The results obtained revealed that the pyridyl/carboxylic acid synthon formed 7/7 times and halogen bonds (N-O…I or N-O…Br) extended the SR/acid dimers into 1D and 2D networks. These results were rationalized via charge calculations as well as through the hierarchical view of intermolecular interactions consisting of hydrogen and halogen bonds. Furthermore, a series of thienyl compounds were synthesized and allowed to react with halogen bond donors to determine whether the halogen bond is purely electrostatic or based on the hard and soft acids and bases principles. The results obtained showed that of the 34 reactions between a halogen bond donor and thienyl compounds, the halogen bond is predominantly electrostatic in nature. Finally, as a result of our improved understanding on molecular recognition, we were able to carry out systematic structure-property studies on a series of cocrystals of anti-cancer drug molecules with aliphatic carboxylic acids. This study revealed that systematic changes to the molecular nature of the co-crystallizing agent combined with control over the way individual building blocks are organized within the crystalline lattice makes it possible to establish predictable links between molecular structure and macroscopic physical properties, such as melting behavior, solubility, dissolution rate, etc.
Keywords: Supramolecular Chemistry; Crystal Engineering; pharmaceutical cocrystal; molecular recognition; self-assembly; Chemistry, Organic (0490)